2016
DOI: 10.14415/zbornikgfs30.03
|View full text |Cite
|
Sign up to set email alerts
|

Analiza Opterećenja Rešetkastog Dalekovodnog Stuba Prema Evropskim Standardima

Abstract: У раду се приказује анализа оптерећења далеководног носивог двосистемског стуба напонског нивоа 110kV према Европским Нормама. С обзиром на специфичност оптерећења које дјелује на далеководни носиви стуб велика труд се мора посветити анализи оптерећења и усвајању случајева оптерећења. Анализирана конструкција је решеткасти челични стуб висине 41,50m са три пара конзола. Након тога, приказује се и дискутује поређење резултата добијених према Европским Нормама са резултатима добијеним према Југословенским станда… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As can been seen in Table 8 Results of the design of the tower elements with loads obtained according to the recommendations given in section 2 and according to EN, [3], are very close. Based on the results of the calculation can be concluded that the load on the power line towers can be calculated by our standards with the recommendations that have been introduced in this paper.…”
Section: Stresses In the Members Of The Tower And Discussionmentioning
confidence: 63%
See 4 more Smart Citations
“…As can been seen in Table 8 Results of the design of the tower elements with loads obtained according to the recommendations given in section 2 and according to EN, [3], are very close. Based on the results of the calculation can be concluded that the load on the power line towers can be calculated by our standards with the recommendations that have been introduced in this paper.…”
Section: Stresses In the Members Of The Tower And Discussionmentioning
confidence: 63%
“…for conductors and ground wires for rectangular cross-section lattice steel tower Unlike European standars in which the load of the wind changes with height above the ground (as shown in [3], tables 3, 4 and 5), according to our standars wind pressure is adopted as constant up to a certain height above the ground [2], Table 1. …”
Section: Wind Loadmentioning
confidence: 99%
See 3 more Smart Citations